Rescue EVAR for ruptured AAA: Clinical success does not mean technical success. (October 2014) - Setacci, Francesco; Sirignano, Pasqualino; de Donato, Gianmarco; Galzerano, Giuseppe; Setacci, Carlo
We report a clinical evolution of a 85-years old male admitted to our Emergency Department for ruptured abdominal aortic aneurysm (rAAA). One month later a huge type I proximal endoleak was detected and corrected by proximal aortic extension. We decided to fix the stent-graft to the aortic wall using EndoAnchors. However, an asymptomatic type III endoleak due to controlateral limb disconnection was detected at the followed schedulated CT angio and corrected by a relining of the endograft. The patient is now in good clinical condition with no evidence of endoleaks at 1-year follow-up.